2011
DOI: 10.1523/jneurosci.2317-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal Connections in Episodic Memory and Aging: A Diffusion MRI Tractography Study

Abstract: Human episodic memory is supported by networks of white matter tracts that connect frontal, temporal, and parietal regions. Degradation of white matter microstructure is increasingly recognized as a general mechanism of cognitive deterioration with aging. However, atrophy of gray matter regions also occurs and, to date, the potential role of specific white matter connections has been largely ignored. Changes to frontotemporal tracts may be important for the decline of episodic memory; while frontotemporal coop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
245
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(279 citation statements)
references
References 76 publications
30
245
3
1
Order By: Relevance
“…Although important for memory performance, we could not assess the fornix in our study because it is not part of the automated atlas we used and it is difficult to delineate this structure when using the tract-based spatial statistics approach. Furthermore, the different sensitivities of the FA and MD parameters led to few overlaps between the FA and MD findings, which has been described in previous neuroimaging studies 7 and did not impact on the interpretation of the results.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Although important for memory performance, we could not assess the fornix in our study because it is not part of the automated atlas we used and it is difficult to delineate this structure when using the tract-based spatial statistics approach. Furthermore, the different sensitivities of the FA and MD parameters led to few overlaps between the FA and MD findings, which has been described in previous neuroimaging studies 7 and did not impact on the interpretation of the results.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have shown that memory function was associated with white matter integrity in the inferior and superior longitudinal fasciculi, the posterior and anterior cingulum 4 the uncinate fasciculus, the dorsal cingulum bundle 5 and the hippocampal part of the cingulum 6 . However, these studies have explored the correlation between episodic memory and white matter integrity in highly-educated individuals, selected under strict criteria from research centers 5,7 . Hence, the role of white matter integrity on episodic memory in community-dwelling elderly with a low educational level remains to be explored.…”
mentioning
confidence: 99%
“…Previous reports using the D&P test had already indicated a selective effect of hippocampal damage on recall (7)(8)(9)(19)(20)(21)(22), but those studies did not examine whether this selective mnemonic effect was correlated with extent of hippocampal damage. Because our patient cohort was a large one and had wide variation in extent of hippocampal atrophy, we were able to examine this structure/function relationship and found a sharp distinction between recall and recognition performance, with only the former showing a correlation with extent of HV loss.…”
Section: Discussionmentioning
confidence: 99%
“…Fornix microstructure accounts for both age-related and age-independent variations in free recall. 5 Recent diffusion MRI studies have found that fornix microstructure is compromised in MCI and Alzheimer disease. 6,7 Early damage might lead to engagement of alternative interactions, 8 so that episodic memory becomes disproportionately associated with microstructure of tracts other than the fornix.…”
mentioning
confidence: 99%